A influência dos fatores predisponentes, capacitantes e de necessidade no uso de serviços odontológicos por crianças aos 12 anos de idade - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Despite the advances in the discovery of the main factors involved in caries and periodontal disease they still remain very prevalent, especially in developing countries. Health behaviors were used to justify this high prevalence, and the use of the dental service is one of the factors with potential impact on the decrease. Thus, the objective of this study was the use of dental services by 12 - year - old children from the Eastern zone of Manaus - AM, using the Theoretical Model of Andersen and Davidson, based on the predisposing, enabling and necessity traits as predictors of the use of services dental services. It was a sectional study, where it was used for the sample as children enrolled in schools of the municipal public network located in the Eastern zone of Manaus and that were in the 7th year of elementary school, through the random process. How schools were selected proportionally to the corresponding number of each neighborhood. Data were collected through self-administered questionnaires and oral clinical exams of the participating children, and by questionnaires answered by items.The sample was of 358 children, located in the 11 districts of the East zone of the city. Those responsible for the children signed the Free and Informed Consent Form (TCLE), the socioeconomic and demographic questionnaire and other instruments (questionnaire that evaluated the sense of coherence and the use of dental services by the child). The children answered the instruments that evaluated the self-esteem, the sense of coherence and the beliefs in oral health. Prior to the initiation of the main study, a pilot study involving 10 children not selected to compose the main study sample was conducted. The examiners were five dentists, trained and calibrated for evaluation of oral health conditions. Data analysis was done using structural equation modeling. The results supported the use of the behavioral model of Andersen and Davidson for this population. All effects were direct, with no indirect or mediated effect. Better socioeconomic status (enabling trait) had a direct effect on the lower need for the use of dental services and a direct effect on a pattern of the use of preventive or restorative dental services. The clinically evaluated need for dental treatment had a direct effect on the greater need for the use of dental services and on a pattern of the use of dental services related to dental urgency (dental pain) or dental extraction. The greater sense of coherence of the responsible (predisposing trait) had a direct effect on the lower use of dental services due to urgency or dental extraction. Being a boy (predisposing trait) had a direct effect on the greater demand to use the dental service and not being attended to. The results confirm that the predisposing factors (gender of the child and sense of coherence), enabling (socioeconomic conditions) and necessity (evaluated) contribute to the use of dental services by children.
Keywords: Serviços de saúde bucal; Saúde bucal; Assistência odontológica; Senso de coerência; Autoestima; CIENCIAS DA SAUDE: ODONTOLOGIA